Cryoballoon ablation of atrial fibrillation in octogenarians: one year results from the Cryo Global Registry. (3rd October 2022) - Lawin, D; Stellbrink, C; Chun, K R J; Lim, H E; Obidigbo, V; Selma, J M; Peytchev, P; Nguyen, D Q; Foldesi, C; Lawrenz, T
Abstract: Background: A few studies have demonstrated the safety and efficacy of cryoballoon ablation (CBA) in elderly patients (≥75 years old) with atrial fibrillation (AF). However, global utilization and outcomes of CBA in the octogenarian population (≥80 years old) have not been reported. Purpose: To evaluate the efficacy and safety of CBA of AF in patients ≥80 years old. Methods: The Cryo Global Registry (NCT02752737) is an ongoing, prospective, multicenter registry. In this analysis, 1674 patients with paroxysmal or persistent AF were included in 37 global centers who treated at least one octogenarian with CBA. Analysis cohorts were defined as patients ≥80 and patients <80 years old (control). To address safety issues of CBA in octogenarians, serious procedure-related complications were assessed. Utilizing Kaplan-Meier estimates, 12-month freedom from a ≥30sec AF/atrial flutter (AFL)/atrial tachycardia (AT) recurrence following a 90-day blanking period was evaluated. Results: The average age of the octogenarians (n=101) was 82±2 years vs 62±10 years in the control group (n=1573). More females were found in the octogenarian population (51.5% vs 35.7%, p<0.01). The ≥80-year-old cohort had lower BMI (26±4 kg/m 2 vs 27±5 kg/m 2 ), higher CHA2DS2-VASc-Scores (4.2±1.3 vs 2.0±1.5), and a higher proportion of heart failure (all p<0.01). The patient cohort ≥80 years was similar compared to the control group regarding the AF history (70.3% vs 74.4% paroxysmal AF), years diagnosed with AF (2.9±4.9 vs 3.2±4.8), and left atrial diameter (43±8 mm vs 42±8 mm) (all p>0.05). Success rates of acute pulmonary vein isolation did not differ between the groups (95.0% vs 96.2%, p=0.59). No differences were observed between ≥80- (5.9%) and <80-year-old patients (3.5%) with respect to serious adverse events (p=0.26). Rhythm monitoring, comprising of Holter and 12-lead ECG, was performed on average 3.1±3.1 times in the elder population and 3.2±3.1 times in the control group through 12 months (p=0.84). Efficacy at 12 months was not different between groups, resulting in 80.6% (95% CI: 71.0–87.3%) freedom from AF/AFL/AT recurrence at 12 months in the octogenarians compared to 78.9% (95% CI: 76.7–80.9%) in the control group (p=0.70). Fewer patients were prescribed AADs at 12 months (32.2%, 23.7%) compared to discharge (47.8%, 49.1%), octogenarians and control, respectively. Further, octogenarians were less likely to receive a repeat ablation 3.3% (95% CI: 1.1–9.7%) in comparison to the control cohort 9.2% (95% CI: 7.8–10.8%) (p=0.052). The 12-month Kaplan-Meier estimate of freedom from cardiovascular-related hospitalization was 81.1% (95% CI: 71.7–87.7%) in the octogenarian and 84.8% (95% CI: 82.9–86.6%) in the control group, respectively (p=0.21). Conclusion: Cryoballoon ablation for the treatment of AF is a safe procedure in octogenarians, with efficacy and complication rates comparable to younger patients. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic, Inc.